2006
DOI: 10.1093/aje/kwj349
|View full text |Cite
|
Sign up to set email alerts
|

Inaccessible Novel Questionnaires in Published Medical Research: Hidden Methods, Hidden Costs

Abstract: and searched portable document format (PDF) versions of the studies for the complete questionnaire or a Uniform Resource Locator (URL) providing access to the questionnaire. When the questionnaire was not provided in the publication or a published URL, the authors requested it from the corresponding author in writing up to three times over a 6-week period. Of 93 publications with novel questionnaires, four printed the questionnaire in the article and three provided online access. Corresponding authors failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
2
17
0
1
Order By: Relevance
“…43 One set of recommended questions to consider when writing a report of findings from postal surveys appears in Table 4. 40 Reviews of the quality of survey reports showed that only 51% included a response rate, 44 8%-16% provided access to the questionnaire, 45,46 and 67% reported validation of the questions. 45 Only with sufficient detail and transparent reporting of the survey's methods and results can readers appraise the survey's validity.…”
Section: Survey Reportingmentioning
confidence: 99%
“…43 One set of recommended questions to consider when writing a report of findings from postal surveys appears in Table 4. 40 Reviews of the quality of survey reports showed that only 51% included a response rate, 44 8%-16% provided access to the questionnaire, 45,46 and 67% reported validation of the questions. 45 Only with sufficient detail and transparent reporting of the survey's methods and results can readers appraise the survey's validity.…”
Section: Survey Reportingmentioning
confidence: 99%
“…In this regard, recommendations have been published for reporting electronic (6) and postal questionnaires (7)(8)(9). Prior research, in areas other than critical care, demonstrates that only 50% of survey reports included a response rate (10), and rarely describe instrument validation (11) or provide direct access to the questionnaires (8%-16%) (11,12).…”
mentioning
confidence: 99%
“…Fifth, the questionnaire should be readily available in the print journal, a journal online supplemental repository or other questionnaire databases (5). Schilling et al found that 37 of 81 (46%) corresponding authors failed to provide the questionnaire used in their study despite repeated contact (5). Readers and reviewers may have increased confidence about the authors' interpretation if they have access to the exact wording of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The reporting of factors key to assessing the methodologic quality and applicability of the results in critical care (2) and anesthesia (3) is poor and inconsistent. In addition, most survey studies do not report response rates (4), and many fail to provide access to their questionnaire (5,6). We conducted this study to describe the quality of reporting of survey studies published between 2001 and 2011 from four high-impact nephrology journals.…”
Section: Introductionmentioning
confidence: 99%